HUMAN DIRECTIONS, DECENT WORK AND PROFISSIONAL TRAINING IN PUBLIC SECURITY: PROPOSAL TO CONFRONT CRIMINOUS FACTS IN RONDÔNIA - Tarciso Pereira da Silva Júnior; Juliana Aparecida Lizo da Cunha; Enoque Vieira da Paixão; Layse Oliveira de Castro; Viviane Souza Oliveira; Jordânia Maria Damasceno; Reinaldo Gonçalves dos Anjos; Cláudia Alessandra Oliveira da Cruz Branco; Cristiana Gomes Rodrigues; Maiara Oliveira Tavares Abraão (Artefactum - revista de estudos interdisciplinares, 2026)
This article analyzes human rights, decent work, and professional training as foundations for an overt and tactical policing model aimed at confronting criminal factions in Rondônia, Brazil. The research asks how a practical, integrated, and territorially oriented response can sustainably reduce criminal organizations’ coercive capacity while preserving lives, evidence, and adequate working conditions. Its objective is to propose the Rondônia Integrated Policing Program against Criminal Factions (PROIFAC-RO), structured in five phases: diagnosis, preparation, intervention, stabilization, and consolidation. The study is qualitative, applied, exploratory, bibliographic, documentary, and propositional. The sources include a 2025 institutional study, research on tactical policing, PMRO teaching guidelines, the National Curriculum Matrix, human rights and decent work standards, legislation on organized crime, and documents concerning the creation of BPTAR. Findings show that arrests and seizures generate more sustainable effects when combined with territorial intelligence, evidence preservation, continued policing, institutional integration, recurrent training, and physical and psychosocial protection for police personnel. The study concludes that human rights and decent work do not restrict police action; they are requirements for legitimacy, operational safety, and effectiveness.